TINGKAT KEPUASAN PELAYANAN KESEHATAN PADA APLIKASI MOBILE JKN DI KOTA TOMOHON - Mantiri, Jeane; Wangkai, Axel; Pongantung, Ronald Jolly; Tarore, Steven (Dinamika : Jurnal Ilmiah Ilmu Administrasi Negara, 2024)
The study aims to identify, describe and analyze the Service Satisfaction Rate of BPJS Health Participants on JKN Mobile Applications in Tomohon City. Data is collected through observation techniques, interviews and interviews as well as documentation. The results of this study, showed the level of satisfaction of the client received by the participants of BPJS Health in Kelurahan Talete Kota Tomohon through online media mobile application JKN related to human resources and applications used. Some officials are not aware of the existence of the Mobile JKN application, and do not receive socialization from any party including BPJS Health. And not all participants can use the mobile JKN app and not all the participants feel at ease with the presence of the mobile application JKN, because at the time of its use there are many obstacles, impediments and problems, such as server errors, features in the application do not work properly, as well as the application often happens updates of the application too often.